The burden of norovirus disease in children: a multi-country study in Chile, Brazil, Thailand and the Philippines. (August 2021) - Safadi, Marco Aurelio; Riera-Montes, Margarita; Bravo, Lulu; Tangsathapornpong, Auchara; Lagos, Rosanna; Thisyakorn, Usa; Linhares, Alexandre C.; Capeding, Rose; Prommalikit, Olarn; Verstraeten, Thomas; O'Ryan, Miguel
Highlights: Norovirus (NoV) was frequent among 1294 children with acute gastroenteritis (AGE). 24% of AGE outpatient episodes and 18% of AGE hospitalizations were NoV-positive. The predominant NoV genotype was GII.4, present in 58% of NoV infections. Brazil, with rotavirus vaccination, had the highest prevalence of NoV infection. ABSTRACT: Background: Noroviruses (NoVs) cause acute gastroenteritis (AGE) worldwide, affecting children in particular. We aimed to estimate the burden of disease due to NoV among children aged <6 years in Brazil, Chile, Philippines and Thailand. Methods: This was a prospective, hospital-based, observational study. Children were recruited over one year between 2014 and 2017. Four cohorts were analysed: community-acquired AGE outpatients and inpatients, nosocomial AGE inpatients, and asymptomatic outpatients. We collected demographic and clinical data, and a stool sample that was tested for NoV. Positive samples were tested for Rotavirus (RV) and NoV-genotyped. Disease severity was assessed by the Vesikari and modified Vesikari scores. Prevalence and incidence of NoV-AGE were estimated by cohort and country. Results: 1637 participants yielded valid laboratory results. The proportion of NoV-positive cases was 23.8% (95% CI 20.8-27.2) in the outpatient cohort, 17.9% (15.0-21.3) in the hospital cohort, 21.4% (12.7-33.8) in the nosocomial cohort and 9.6% (6.9-13.2) in the asymptomatic cohort. Genotype GII.4 was predominant (58%). Less than 4% samples had RV coinfection. In general, NoV-positive subjects had more severe presentations than NoV-negative subjects. Conclusions: NoV caused AGE with substantial burden throughout the studied settings, with higher relative frequency in Brazil where RV vaccination coverage is high.